2013
DOI: 10.2485/jhtb.22.13
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Ions Released from Mineral Trioxide Aggregate are Taken Up by C2C12 Cells via the L-Type Voltage-Dependent Calcium Channel

Abstract: Mineral trioxide aggregate (MTA) is a commonly used endodontic repair material reported to exhibit calcified-tissue conductive activity. The effect of MTA on osteoblast differentiation has been well-defined; however, its effect on mesenchymal cells is not fully understood. Recently, we reported that MTA converts the differentiation pathway of pluripotent mesenchymal cells (C2C12 cells) into osteoblast lineages, possibly through the influx of elution components, such as calcium ions released from MTA. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In particular, the increase in the concentration of calcium ions guides cells through mitosis via different mechanisms such as nuclear envelope breakdown, chromosome condensation, spindle fiber formation, and sister chromatid separation [54]. In MTA, calcium ions are present as calcium oxide which reacts with tissue fluids, forming calcium hydroxide [56]. Studies that have evaluated the effect of increasing the concentration of calcium ions in MTA have found that there is a limit to the effect of calcium ions on cellular mineralization [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the increase in the concentration of calcium ions guides cells through mitosis via different mechanisms such as nuclear envelope breakdown, chromosome condensation, spindle fiber formation, and sister chromatid separation [54]. In MTA, calcium ions are present as calcium oxide which reacts with tissue fluids, forming calcium hydroxide [56]. Studies that have evaluated the effect of increasing the concentration of calcium ions in MTA have found that there is a limit to the effect of calcium ions on cellular mineralization [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the alkaline pH provides bacteriostatic effects 45 and can promote apical healing and tissue mineralization 36 . Whereas the release of calcium ions, which are strong extracellular signals for undifferentiated cells 46 , is important for healing of apical periodontitis associated with bone resorption. Results of our study showed that VDW.1Seal exhibited the highest alkalinity and the highest cumulative calcium ion release compared to the other sealers at the end of the observation period ( p ≤ 0.05).…”
Section: Discussionmentioning
confidence: 99%